Early growth and dry matter yield of gmelina arborea (roxb) on basement complex and ferric luvisol soils (2009)
The study investigated the use efficiency of selected soil nutrient elements-N, P and K in the synthesis of organic matter by Gmelina arborea seedlings. Gmelina arborea (family: Verbamacaea) seedlings were grown on basement complex and ferric luvisol soils for 3-months. Sixty polythene pots were filled with each soil type, which formed an experimental unit. Each experimental unit was replicated three times making a total of 360 Gmelina arborea seedlings. Eight seedlings were selected weekly for the first four weeks and four seedings per week for the remaining six weeks in each experimental unit. Composite samples of soil media and sampled seedling were taken weekly and chemically analyzed for the determination of possible changes in nutrient concentrations. The dried leaves and shoot were combusted at 500°c, for carbon content determination. Student t-test shows no significant difference in biomass carbon between basement complex and ferric luvisol soils (paired sampled t-test, 80.92 vs 80.35g/kg, respectively, p<0.05, n=10). Significant relationship exists between leaf area ratio (LAR) and leaf weight ratio (LWR) of seedlings grown on both soil types. Thus, P and N provide a much sensitive measure of the relative cost of dry matter production than potassium in these soils. The study highlights quantitative relationships that would allow silviculturists to estimate accurately the phosphorus and nitrogen-supplying power of basement complex and ferric luvisol soils.